Cognitive factors in adjustment after social trauma - Graham, B (2022)
This project uses mixed methods to investigate cognitive and behavioural factors associated with social anxiety disorder (SAD) and posttraumatic stress disorder (PTSD) symptoms among young people who have been bullied. The aim is to explore the social trauma of bullying, investigate factors that increase vulnerability to ongoing emotional distress, and develop bespoke measures that are clinically useful and statistically robust.